The Use Of Internet In Supplier Selection Process And Managerial Performance In The Northern Region Of Peninsular Malaysia - Lim, Tony Swee King (2005)

(untitled)
Sebagaimana yang diketahui, kos bahan mentah mengambil sebahagain besar jumlah kos produk